2016
DOI: 10.1039/c6fo00203j
|View full text |Cite
|
Sign up to set email alerts
|

Blue honeysuckle fruit (Lonicera caerulea L.) from eastern Russia: phenolic composition, nutritional value and biological activities of its polar extracts

Abstract: In the present work we conducted a comprehensive chemical analysis of blue honeysuckle (Lonicera caerulea) spontaneously growing in eastern Russia. HPLC-DAD-ESI/MS analysis showed cyanidin-3-glucoside as the major constituent among phenolics, while nutritional analysis revealed fibre, protein, calcium and magnesium as the most important macro- and micronutrients, respectively. Fatty acid composition was dominated by polyunsaturated fatty acids, linoleic acid being the most abundant. Furthermore, we evaluated s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 45 publications
3
33
0
Order By: Relevance
“…The LCPs were extracted following the protocols described in the authors’ previous study and stored at −20 °C until use. [ 27 ] l ‐(+)‐ascorbic acid (Vc standard, HPLC ≥ 98.0%) was purchased from Putian Tongchuang Biotechnology Co., Ltd. (Beijing, China).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The LCPs were extracted following the protocols described in the authors’ previous study and stored at −20 °C until use. [ 27 ] l ‐(+)‐ascorbic acid (Vc standard, HPLC ≥ 98.0%) was purchased from Putian Tongchuang Biotechnology Co., Ltd. (Beijing, China).…”
Section: Methodsmentioning
confidence: 99%
“…Lonicera caerulea L. berries are widely harvested in northeast Russia, China, Japan, and Canada. [ 25 ] Previous studies have reported that polyphenols, including anthocyanins (mainly anthocyanin‐3‐glucoside), phenolic acids (gentisic acid, chlorogenic acid, caffeic acid, and ellagic acid), and flavonoids (catechin, quercetin‐3‐glucoside, and quercetin‐3‐rutinoside), are the main bioactive compounds in L. caerulea L. [ 26 ] These polyphenols exhibit a wide range of physiological functions, [ 27‐28 ] such as reducing cholesterol, [ 29 ] alleviating lung fibrosis, [ 25 ] and moderating non‐alcoholic steatohepatitis. [ 30 ] Previously, we had reported that L. caerulea L. polyphenols (LCPs) can inhibit LPS‐induced liver damage in rats.…”
Section: Introductionmentioning
confidence: 99%
“…These authors also reported a higher content of C3G in honeysuckle (L. caerulea) than in blueberries (1.77 mg/g vs. 0.02 mg/g). Caprioli et al (2016) reported for haskap berries spontaneously growing in eastern Russia an anthocyanin content of 12.3 mg/g dry weight which corresponded to approximately 1.5 mg/g fresh berries. Caprioli et al (2016) reported for haskap berries spontaneously growing in eastern Russia an anthocyanin content of 12.3 mg/g dry weight which corresponded to approximately 1.5 mg/g fresh berries.…”
Section: Compositional Datamentioning
confidence: 92%
“…The total phenolic content is expressed as gallic acid equivalents (GAE) per g of dry meat. The results are expressed as the average of three determinations/animal (Caprioli et al, 2016). Protein concentrations of tissue lysates were determined by the Bradford protein assay (Compton & Jones, 1985) to express the GSHPx activity as U/mg of protein (Stables & Gilroy, 2011).…”
Section: Meat Sampling Total Phenolic Content Measurement and Gshpx mentioning
confidence: 99%